2011
DOI: 10.2147/rrn.s23987
|View full text |Cite
|
Sign up to set email alerts
|

PETCO2 measured by a new lightweight mainstream capnometer with very low dead space volume offers accurate and reliable noninvasive estimation of PaCO2

Abstract: Objective: Although capnometers are widely used in adult and pediatric intensive care units, they are not widely used in neonatal intensive care units due to issues such as the weight of sensors, dead space, and leakage from tracheal intubation tubes. These authors developed a light and low dead space airway adaptor of end-tidal carbon dioxide pressure (P ET CO 2 ) and evaluated the correlations between P ET CO 2 and partial CO 2 pressure (PaCO 2 ) in rabbits while changing tidal volume and leakage volume. Met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…Figure 2 shows the quadratic discriminant analysis for VT and percentage of ETT leak. The differences between ETCO 2 and PaCO 2 (bias) were compared to the bias of a previous study [ 7 ] to determine the degree of agreement between ETCO 2 and PaCO 2 . A discrimination analysis for the VT and the percentage of ETT leak yielded 70.4% [95% CI, 65.1 to 75.7] discrimination for the agreement between ETCO 2 and PaCO 2 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Figure 2 shows the quadratic discriminant analysis for VT and percentage of ETT leak. The differences between ETCO 2 and PaCO 2 (bias) were compared to the bias of a previous study [ 7 ] to determine the degree of agreement between ETCO 2 and PaCO 2 . A discrimination analysis for the VT and the percentage of ETT leak yielded 70.4% [95% CI, 65.1 to 75.7] discrimination for the agreement between ETCO 2 and PaCO 2 .…”
Section: Resultsmentioning
confidence: 99%
“…And if the discriminant function is negative ( Z < 0), there is no agreement between ETCO 2 and PaCO 2 . We defined a bias (ETCO 2 –PaCO 2 ) level of −6.74 mmHg as the acceptable lower limit for the difference between ETCO 2 and PaCO 2 based on our previous experiments examining ETCO 2 in rabbits [ 7 ], which showed that the limits of agreement were −6.74 to 4.99 mmHg based on Bland–Altman plots. Values of p < 0.05 were determined to be significant.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The mainstream capnography probe and mask invented by Nihon Kohden have been tested in nonintubated adults (12,13,15). The cap-ONE infant and pediatric masks have been specifically designed for (Figure 1a) (14).…”
Section: Discussionmentioning
confidence: 99%
“…We have previously reported a strong correlation between P ET CO 2 and PaCO 2 under controlled ventilation when tidal volume/body weight (TV/BW) was 6 -15 mL/kg and the leakage rate was <60% in rabbits. Furthermore, under conditions of 6 mL/kg of tidal volume (TV), PaCO 2 was significantly increased by a dead space increase of only 1 mL, representing >7% of TV [4].…”
Section: Introductionmentioning
confidence: 99%